Differences between CTAB and chitosan in modifying PLGA nanoparticles for gene therapy - Doolaanea, Abd Almonem; Mansor, Nur 'Izzati; Mohd Nor, Nurul Hafizah; Mohamed, Farahidah (UKM Kuala Lumpur Campus, 2015)
Poly (D, L-Lactic-co-Glycolic Acid) (PLGA) nanoparticles were modified by adding cetyltrimethylammonium bromide (CTAB) to the aqueous phase (F1) or oil phase (F2), or by low (F3) or medium (F4) molecular weight chitosan. Nanoparticles were characterised for their physicochemical and biological properties. CTAB was found to adsorb on the surface of F1 with easy desorption. This led to negative zeta potential, high cytotoxicity and low cell uptake/transfection. F2 exhibited negative zeta potential, low cytotoxicity, and higher cell uptake/transfection. F3 and F4 showed positive zeta potential, low cytotoxicity and high cell uptake/transfection. Due to its stronger interaction with PLGA that may stabilise the plasmid DNA, F4 exhibited higher transfection efficacy. This study highlights the significant differences between CTAB and chitosan in modifying nanoparticles for gene therapy.